2014
DOI: 10.1007/s00038-014-0568-4
|View full text |Cite
|
Sign up to set email alerts
|

Children’s awareness of alcohol sponsorship of sport in Ireland: Munster Rugby and the 2008 European Rugby Cup

Abstract: These findings support the view for an immediate introduction of legislation banning the sponsorship of sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Curiosity is also one of the reasons why users were interested in this device, and the rather high prevalence of ever use can be explained in part by the novelty of the product and also by the fact that young adults and college students are more inclined to try new products and respond to marketing and publicity campaigns 6 49 since aggressive sponsorship has been shown to induce higher alcohol awareness in children. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Curiosity is also one of the reasons why users were interested in this device, and the rather high prevalence of ever use can be explained in part by the novelty of the product and also by the fact that young adults and college students are more inclined to try new products and respond to marketing and publicity campaigns 6 49 since aggressive sponsorship has been shown to induce higher alcohol awareness in children. 52 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, most research to date on the effects of exposure to alcohol promotion has examined alcohol advertising in general and relatively little work has focused on the outcomes specifically around sports-related communications. Consistent with the broader body of work, the limited research on alcohol promotion in sporting-related contexts indicates that exposure results in young people: 1) associating sport with both alcohol in general and particular products and brands (Bestman et al, 2015;Houghton et al, 2014;Pettigrew et al, 2013b); and 2) being more likely to consume alcohol more frequently and to engage in heavy episodic drinking (de Bruijn et al, 2016). In addition, studies of the drinking behaviours of university and community club athletes have found that those sponsored by alcohol companies are more likely than other athletes to engage in hazardous levels of alcohol consumption (for a review, see Brown, 2016).…”
Section: Effects Of Exposure To Alcohol Promotion In Sports-related Cmentioning
confidence: 86%
“…Much of the research on sponsorship and alcohol has focused on children and underage youths (in their countries of residence) and on the relationship between sponsorship (e.g., Houghton, Scott, Houghton, & Lewis, 2014) and the intention to consume (Kelly, Bauman, & Baur, 2014a). The conclusion is that the image is transferred to the brand., but with a very low intention to consume (only 25%).…”
Section: The Dilemma Of the Effectiveness Of Alcohol Brand Sponsorshipmentioning
confidence: 99%